2008
DOI: 10.1021/ac800521z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrode Roughness On the Capacitive Behavior of Self-Assembled Monolayers

Abstract: Analytical gold electrodes were polished mechanically and electrochemically and the true area of the electrode surface was measured by quantitative oxidative/reductive cycling of the electrode. A roughness factor for each electrode was determined from the ratio of the true area to the geometric area. The roughness is fully described by a combination of microscopic roughness (up to tens of nanometers) and macroscopic roughness (on the order of hundreds of nanometers) terms. The electrodes were then derivatized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 38 publications
(121 reference statements)
6
43
0
Order By: Relevance
“…The roughness, which is defined by the ratio of the true to the geometric surface area, is around 2.7. This value is similar to the one for a macroelectrode [26].…”
Section: Instrumentation and Proceduressupporting
confidence: 84%
“…The roughness, which is defined by the ratio of the true to the geometric surface area, is around 2.7. This value is similar to the one for a macroelectrode [26].…”
Section: Instrumentation and Proceduressupporting
confidence: 84%
“…The elements of this equivalent electric circuit are the C dl , which models the interfacial capacitance that arises from the double layer capacitance at the film/ electrode interface, and R b and C b , associated in parallel, which represent the bulk resistance and the geometrical capacitance of the film/electrode interface, respectively. As the real system is much more complicated and the capacitance at solid electrodes does not behave ideally, two constant phase elements substitute the capacitors C dl and C b considering the inhomogeneity of the system and the roughness and irregularities of the electrode surface [48,49]. After fitting the experimental data to an equivalent electrical circuit it was found that PLA and PLA-P3TMA blends of wt% ratio 5:1 and 2:1 adjust to the circuit depicted in Figure 6c, while the fitting of a circuit to the 1:1 blend was much more difficult to achieve.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 99%
“…1 using the nonlinear least squares fitting routine provided by the ZView software program. A constant phase element (CPE) was used to model the interfacial capacitance, to account for deviations from ideal capacitive behavior [24,25] and to achieve a more accurate fit to the experimental data. The impedance of a CPE is given by (Q(ix) n ) À1 , and is equivalent to an ideal capacitor when the CPE exponent, n, is equal to 1.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…However, in situations where the CPE exponent is slightly less than one but constant over a potential window or solution conditions, it is a fair approximation to use the magnitude of the CPE parameter as the film's capacitance. In our experiments, we observed a change in the CPE exponent over the potential window of interest and, to account for this change, converted the magnitude of the CPE (Q) into an effective capacitance (C) using the following correction [24,38,39]:…”
Section: Reversible Permeability Of Ld-mha Samsmentioning
confidence: 99%